THE ENERGY-STATES OF EXCITONS IN A HARMONIC QUANTUM-DOT - ELSAID, M (Akademie Verlag Gmbh, 1994)
The eigenenergies of low-lying states of excitons in a quantum dot with a harmonic confining potential are obtained by solving the effective-mass Hamiltonian using the shifted 1/N expansion method. The ground state binding energy is in excellent agreement with previous results.
Keywords: Hydrogenic Donor States; Magnetic-Field; Confinement; Well; Electrons; Strengths; Expansion; Boxes; Gaas